Effect of One-Time Application of Biochar and Compost on Soil and Maize During 5-Time Consecutive Periods of Crop Cultivation - Wijitkosum, Saowanee; Sriburi, Thavivongse; Toonsiri, Phasita (Ital Publication, 2025)
This study evaluates the impact of a single-time biochar application during initial cultivation on the performance of five consecutive crop cycles. The research compares the effects of biochar alone versus biochar combined with soybean compost on maize yield and soil properties over a period of 2.8 years. Fundamental soil properties—including pH, cation exchange capacity, organic matter content, and macronutrient levels—were assessed before each planting cycle and at the end of the fifth cycle. Maize yield and productivity were evaluated based on the number of maize ears, kernel biomass, and both fresh and dry kernel weights. Five experimental plots, each with four replicates, were established with the following treatments: compost applied at 0.56 kg/sq m (TM), cassava stem (CS) biochar applied alone at 2.5 kg/sq m (TB2.5) and 3.0 kg/sq m (TB3.0), and combinations of compost at 0.56 kg/sq m with CS biochar at 2.5 kg/sq m (TMB2.5) and 3.0 kg/sq m (TMB3.0). Results indicated that the sole application of biochar and its combination with compost positively affected soil properties and maize yield. Biochar applications alone significantly improved soil nutrient levels and maize yields compared to the compost alone. Notably, the beneficial effects of biochar on maize and soil were observed from the first cultivation and persisted throughout all five cycles. Based on these findings, it is recommended to apply biochar at 3.0 kg/sq m, in combination with compost at 0.56 kg/sq m, every three crop cycles to sustain nutrient levels and enhance maize yields effectively. Doi: 10.28991/ESJ-2025-09-01-07 Full Text: PDF